Teacher Expectations and Parental Stress During Emergency Distance Learning and Their Relationship to Students’ Perception - Garrote, Ariana; Niederbacher, Edith; Hofmann, Jan; Rösti, Ilona; Neuenschwander, Markus P. (Frontiers in Psychology, 2021)
School closures in spring 2020 caused by the COVID-19 pandemic were an unprecedented and drastic event for students, parents, and teachers. The unplanned adaptation of classroom instruction to emergency distance learning was necessary to ensure continued education. In this new learning environment, teachers formed expectations for student academic achievement gains, which in turn affected the opportunities for students to learn. Parents faced new challenges in supporting their children’s learning. According to parenting stress models, such drastic events can be a stress factor for parents, which in turn affects their children’s adjustment. This study analyzed the extent to which parents and teachers affected the perceptions of students in compulsory school toward distance learning through processes at home (individual level) and at the class level with data from multiple informants. On an individual level, the relationship between parents’ perceived threat of COVID-19 and their stress due to distance learning and students’ perceived threat of COVID-19 and their perception of distance learning were examined. Students’ learning behavior was accounted for as a variable related to their perception of distance learning. At the class level, the explanatory character of teacher expectations and class-aggregated achievement gains were examined. Data on students in grades 4 to 8, parents, and teachers in Switzerland were collected with standardized online questionnaires after the period of school closures. A subsample of 539 students, 539 parents, and 83 teachers was analyzed. The results of multilevel structural equation modeling suggested that students had a more positive perception of distance learning if they were able to learn more autonomously (i.e., more motivated and concentrated than in regular classroom instruction) and if their parents felt less stressed in the distance learning setting. Parents were more stressed if they perceived COVID-19 as a threat. Students’ perception of the COVID-19 threat was related to their parents’ perception but did not explain students’ learning behavior. At the class level, if teachers expected high academic achievement gains in distance learning, the average academic achievement gains of a class were greater. The greater the achievement gains were, the more positive the collective student perception of distance learning was.